1991
DOI: 10.1056/nejm199111143252002
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Supplementation to Prevent Hypertensive Disorders of Pregnancy

Abstract: Pregnant women who receive calcium supplementation after the 20th week of pregnancy have a reduced risk of hypertensive disorders of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(81 citation statements)
references
References 24 publications
3
75
1
2
Order By: Relevance
“…Recent evidence suggests that calcium could also increase magnesium levels and have an effect on smooth muscle function of the uteroplacental blood flow 17 . Despite the results of some previous studies about a relation between calcium supplementation and gestational age and lower rates of preterm birth 18,19 , our finding showed that there are no differences in pregnancy outcome such as preterm birth, low birth weight, NICU admission, and low Apgar scores between the two groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent evidence suggests that calcium could also increase magnesium levels and have an effect on smooth muscle function of the uteroplacental blood flow 17 . Despite the results of some previous studies about a relation between calcium supplementation and gestational age and lower rates of preterm birth 18,19 , our finding showed that there are no differences in pregnancy outcome such as preterm birth, low birth weight, NICU admission, and low Apgar scores between the two groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, intake of calcium has been shown to correlate inversely with blood pressure in clinical and experimental studies (9), although some contradictory results have also been published (10). Calcium supplementation has also been suggested to decrease blood pressure in human hypertension, and certain types of hypertensive patients, including those with hypertensive disorders of pregnancy and salt-sensitive individuals, may be more susceptible to the blood pressure-lowering action (11).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore consider supplementation at 20 weeks to be benefi cial. [19][20][21] Still unproven (unknown, not enough evidence)…”
Section: Calciummentioning
confidence: 99%